Dirasat wa abhath fi al-adab al-'Arabi - Rabi', Muhammad Ahmad ('Amman : Mu'assasah al-Waraq, 2011)
Arabic poetry; Arabic literature; history and criticism
Includes bibliographical references.
Keywords: Arabic poetry -- History and criticism; Arabic literature -- History and criticism